Effects of Tasks on Spoken Interaction and Motivation in English Language Learners - Carrero Pérez, Nubia Patricia (GIST – Education and Learning Research Journal, 2016)
Task based learning (TBL) or Task based learning and teaching (TBLT) is a communicative approach widely applied in settings where English has been taught as a foreign language (EFL). It has been documented as greatly useful to improve learners’ communication skills. This research intended to find the effect of tasks on students’ spoken interaction in English and motivation towards speaking English in the classroom. Thirty-five adolescent tenth grade students from a public school in Bogota, Colombia, participated in the study. They reported positive influence of tasks in their English oral interaction improvement as well as on their motivation towards speaking English in the classroom.